2013
DOI: 10.1038/jhg.2013.59
|View full text |Cite
|
Sign up to set email alerts
|

A replication study for three nephrolithiasis loci at 5q35.3, 7p14.3 and 13q14.1 in the Japanese population

Abstract: A previous genome-wide association study (GWAS) reported three novel nephrolithiasis-susceptibility loci at 5q35.3, 7p14.3 and 13q14.1. Here, we investigated the association of these loci with nephrolithiasis by using an independent Japanese sample set. We performed case-control association analysis using 601 patients with nephrolithiasis and 201 control subjects. We selected seven single-nucleotide polymorphisms (SNPs): rs12654812 and rs11746443 from 5q35.3 (RGS14-SLC34A1-PFN3-F12); rs12669187 and rs1000597 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 27 publications
2
39
0
1
Order By: Relevance
“…In the replication study, SNP rs12669187, located on FAM188B gene, also showed a significant association with nephrolithiasis7. The role of FAM118B in the pathogenesis of nephrolithiasis has not been fully elucidated so far.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the replication study, SNP rs12669187, located on FAM188B gene, also showed a significant association with nephrolithiasis7. The role of FAM118B in the pathogenesis of nephrolithiasis has not been fully elucidated so far.…”
Section: Discussionmentioning
confidence: 94%
“…conducted a GWAS using a total of 5892 nephrolithiasis cases and 17809 controls of Japanese population and found three novel loci for nephrolithiasis, including rs11746643 on 5q35.3, rs100597 on 7p14.3 and rs4142110 on 13q14.1. Yasui et al 7. performed a replication study for these three loci and their results have reported that rs12654812 on 5q35.3, rs12669187 on 7p14.3 and rs7981733 on 13p14.1 were significantly associated with nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, renal Mws sorted from op/op mice expressed lower levels of stone-and M2-related genes based on microarray analysis. Some genes listed in Figure 10A (such as Aqp1, Aurka, and Slc34a1) inhibit the development of renal stones, 53,54 suggesting that CSF-1 deficiency resulted in severely impaired defense against crystal formation in Mws. hi M2-like Mws by CSF-1 treatment reduced renal crystal deposition and CaOx crystal formation.…”
Section: Discussionmentioning
confidence: 99%